Five new malformed trilobites from Cambrian and Ordovician deposits from the Natural History Museum - Bicknell,Russell D.C.; Smith,Patrick M. (PeerJ, 2023)
Injured trilobites present insight into how a completely extinct group of arthropods responded to traumatic experiences, such as failed predation and moulting complications. These specimens are therefore important for more thoroughly understanding the Paleozoic predator-prey systems that involved trilobites. To expand the record of injured trilobites, we present new examples of injured Ogygopsis klotzi and Olenoides serratus from the Campsite Cliff Shale Member of the Burgess Shale Formation (Cambrian, Miaolingian, Wuliuan), Paradoxides (Paradoxides) paradoxissimus gracilis from the Jince Formation (Cambrian, Miaolingian, Drumian), Ogygiocarella angustissima from the Llanfawr Mudstones Formation (Middle–Late Ordovician, Darriwilian–Sandbian), and Ogygiocarella debuchii from the Meadowtown Formation, (Middle–Late Ordovician, Darriwilian–Sandbian). We consider the possible origins of these malformations and conclude that most injuries reflect failed predation. Within this framework, possible predators are presented, and we uncover a marked shift in the diversity of animals that targeted trilobites in the Ordovician. We also collate other records of injured Ogygo. klotzi and Ol. serratus, and Ogygi. debuchii, highlighting that these species are targets for further understanding patterns and records of trilobite injuries.
Keywords: Trilobites; Injuries; Predator-prey systems; Predation; Paleozoic; Burgess Shale; Jince formation; Llanfawr Mudstones Formation; Meadowtown Formation